Mapping the anatomy of a Plasmodium falciparum MSP-1 epitope using pseudopeptide-induced mono- and polyclonal antibodies and CD and NMR conformation analysis (2004)
Antigen structure modulation represents an approach towards designing subunit malaria vaccines. A specific epitope's ? carbon stereochemistry, as well as its backbone topochemistry, was assessed for obtaining novel malarial immunogens. A variety of MSP-138–61 Plasmodium falciparum epitope pseudopeptides derived were synthesised, based on solid-phase pseudopeptide chemistry strategies; these included all-l, all-d, partially-d substituted, all-?-[NH-CO]-Retro, all-?-[NH-CO]-Retro-inverso, and ?-[CH2NH] reduced amide surrogates. We demonstrate that specific recombinant MSP-134–469 fragment binding to red blood cells (RBCs) is specifically inhibited by non-modified MSP-142–61, as well as by its V52-L53, M51-V52 reduced amide surrogates and partial-d substitutions in K48 and E49. In vivo tests revealed that reduced amide pseudopeptide-immunised Aotus monkeys induced neutralising antibodies specifically recognising the MSP-1 N-terminus region. These findings support the role of molecular conformation in malaria vaccine development.